Is pyroptosis a brake or an accelerator in the fate of the tumor? - Yixuan Hou; Wei Li; Jiaying Yang; Haoyang Yu; Congcong Wang; Yanru Li; Shuang Lv; Ling Zhang (Cell Death and Disease)
Abstract Cancer currently stands as a formidable challenge confronting humanity. Patients afflicted with malignancies typically endure diminished survival rates and compromised quality of life. Consequently, the paramount objective of oncological research lies in redefining cancer from a terminal diagnosis to a clinically manageable condition, thereby realizing this transformative medical paradigm. The development of multiple innovative therapeutic strategies may enhance the antitumor immune response. Notably, pyroptosis is considered both a form of programmed cell death and a highly inflammatory type of immunogenic cell death. Its activation may accelerate cancer cell death and exert antitumor effects as a promising scenario to reverse immunosuppression. This article elaborates on the following three main aspects: the molecular mechanisms underlying pyroptosis and the development of promising therapeutics that target pyroptosis, the relationship between pyroptosis, inflammation, and tumors, and the application of nano-targeting materials in tumor treatments. These interactive therapeutic patterns may catalyze a paradigm shift in oncology. In this review, we probe the synergistic effects of pyroptosis and nanomaterials, forecast achievements in the field of tumor treatments, detail optimized therapeutic strategies, and shed promising light on the potential for the improvement and development of clinical drugs based on pyroptosis.